2022
DOI: 10.1186/s40001-022-00635-w
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of sexually transmitted infections and risk factors among HIV-positive individuals in Yunnan, China

Abstract: Background Yunnan has the highest rates of HIV in China. Other treatable sexually transmitted infections (STIs) are associated with accelerated HIV transmission and poor ART outcomes, but are only diagnosed by syndromic algorithms. Methods We recruited 406 HIV-positive participants for a cross-sectional study (204 ART-naive and 202 receiving ART). Blood samples and first-voided urine samples were collected. Real-time polymerase chain reaction metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…A total of 205 full-text articles were assessed for eligibility, of which 176 were excluded (description of excluded studies is recorded in Supplementary Table 2 ). Finally, 29 studies were included in this meta-analysis ( 22 50 ). The flow chart of our systematic literature search is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 205 full-text articles were assessed for eligibility, of which 176 were excluded (description of excluded studies is recorded in Supplementary Table 2 ). Finally, 29 studies were included in this meta-analysis ( 22 50 ). The flow chart of our systematic literature search is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Although CT infection is very common throughout the world, there are few studies on the prevalence of CT in people living with HIV/AIDS (PLHA). Recent studies show that the prevalence of CT in PLHA varies from 3.2% to 12.5% in populations from different countries [ 9 , 10 , 11 ]. In Brazil, the prevalence of CT infection in PLHA is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“… 22 The HIV infection enhancement can be because of various processes, such as the disturbance of normal epithelial barriers with ulcerations, causing the recruitment of HIV-susceptible T-lymphocytes or macrophages to the infected area as part of the host’s immune response. 22 , 23 Human immunodeficiency virus-infected persons are more likely to be coinfected with chronic herpesviruses, which replicate periodically producing viable herpes virions. 24 A South African study revealed that contracting either HIV or HSV-2 will encourage infection by the other.…”
Section: Introductionmentioning
confidence: 99%